Impact of Intellectual Capital, Islamicity Performance Index, and Corporate Governance on Bank Profitability: Empirical Evidence from Indonesian Islamic Commercial Banks - Akbar, Zoramchev; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aims to analyze the influence of Intellectual Capital, Islamicity Performance Index, and Good Corporate Governance on Bank Profitability, specifically focusing on Islamic Commercial Banks in Indonesia from 2016 to 2021. The sample selection utilized the Purposive Sampling method, resulting in a total of eight companies being included. Multiple linear regression analysis was employed to examine the effect of each variable on Return On Assets (ROA). The findings indicate that Intellectual Capital has a significant impact on ROA, while Profit Sharing Ratio does not affect ROA. Furthermore, Zakat Performance Ratio, Sharia Supervisory Board, and Audit Committee were found to have a significant influence on ROA. Data for this study were collected from secondary sources, primarily financial reports and published Good Corporate Governance disclosures on the respective websites of Indonesian Islamic Commercial Banks. The research contributes to the understanding of factors influencing bank profitability and provides valuable insights for policymakers, practitioners, and researchers in the field of Islamic finance and banking. Highlight: Intellectual Capital, Zakat Performance Ratio, Sharia Supervisory Board, and Audit Committee have a significant impact on Return on Assets, influencing bank profitability. Profit Sharing Ratio does not affect Return on Assets, indicating its limited influence on bank profitability. This study provides empirical evidence on the relationship between various factors, such as Intellectual Capital and corporate governance, and their impact on bank profitability in the context of Islamic Commercial Banks in Indonesia. Keyword: Bank Profitability, Intellectual Capital, Islamicity Performance Index, Good Corporate Governance, Return on Assets